Тайный друг: [роман] / Крис Муни - Муни Крис (Клуб Семейного Досуга, 2009)
Экземпляры: ф.12 (20190416) / Инвентарный номер: 59436 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: М 90 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44